Mk4 Kiln In Brick Manufacturing In Peru: Reduction Of Pollutants And Maximum Energy Efficiency For Sustainable Production - Huaman Diaz, Maria Fernanda (2024)
The study of the MK4 kiln reveals notable results, highlighting its efficiency in firing bricks through convection heat exchange, avoiding heat losses in kilns (1) and (2), achieving a final firing temperature of 995.6 °C in 160 min, this system not only accelerates the cooking process, but also contributes significantly to the overall efficiency, benefiting comprehensive operational efficiency not only improves the quality of the final product, but also promotes sustainability and profitability in the manufacture of bricks, indicating a faster and more uniform firing. Likewise, it demonstrates optimal results in its cogeneration system, having an energy efficiency of 60% in 160 min of cooking, generating a heat recovery temperature of 596.5 °C in each oven (3) and (4). In addition, the pollutants PM2.5 and PM10, through the gravitational force, the particles settle during the cooking process and remain within the environmental quality standards, registering 23 μg/m3 and 60 μg/m3, respectively. Finally, the MK4 oven is presented as an effective and sustainable solution, surpassing inefficient and polluting artisanal ovens. Marking a milestone in the search for environmental sustainability and efficiency in the brick production industry, allowing an impact on the firing time and, therefore, on the quality of the final product that allows improving the quality of life of the society and environment.